Penerapan Fuzzy Inference Model Takasi-Sugeno-Kang Pada Sistem Pakar Diagnosa Penyakit Usus Manusia - Moda Awa, Aristo; Kopong Pati, Gergorius; Malo Ngongo, Martinus (JOURNAL OF ELECTRICAL AND SYSTEM CONTROL ENGINEERING, 2024)
The digital era, it is possible for everyone to do anything, including documenting or getting solutions related to a disease, such as in this research which was carried out to diagnose intestinal disease. As a lay person, of course you will be confused by the symptoms or problems that arise when you encounter an illness. This is the background for designing and creating the application of the Takasi-Sugeno-Kang Fuzzy Inference System in an Expert System for Diagnosing Colon Diseases in Humans, with various methods to produce applications that will be created starting from interviews with expert technicians to determine the various parameters that will be used to selecting the Certainty Factor probability as a calculation algorithm for system design and implementation. The results of the application of the Takasi-Sugeno-Kang Fuzzy Inference System in the Expert System for Diagnosing Intestinal Diseases in Humans can diagnose damage or disease in tobacco plants along with what type of disease occurs and alternative solutions. After making this application it can help doctors in preventing intestinal diseases.